IMPLEMENTASI PERDA NOMOR 1 TAHUN 2012 TENTANG PAJAK DAERAH TERHADAP KEPATUHAN MEMBAYAR PAJAK BUMI BANGUNAN DI KABUPATEN TEGAL - ASLANI, ASLANI (Dinamika Hukum, 2016)
Background Local tax is one source of revenue is important and a potential addition to other sources of income, namely oil and gas revenues and non-tax revenues due to the number of population is so large and the area is so large, the Tegal has tax sources very much. Receipts from taxes is then used by the government to build infrastructure in the public interest. In other words, the local revenue from taxes is a